Potentiotitrimetric Determination of Isoniazid Using Twin Copper Based Mercury Film Electrode - Lakshmi, L. (Asian Journal of Chemistry, 2010)
This study deals with the quantitative determination of isoniazid by employing twin copper based mercury film electrode of different lengths to improve the analytical power of detection and the reliability of the results gained and to improve the economy of the method employed for the routine determination of isoniazid in pharmaceutical formulations. The electrode is specialy fabricated for this titration.